Design, synthesis, and anticancer activity of three novel palbociclib derivatives - Li, Tian; Zhou, An-Di; Bai, Li-Fei; Zhang, Xiao-Yang; Zhou, Yu-Ting; Yang, Hai-Li; Xu, Le-Tian; Guo, Xin-Qin; Zhu, Xi-Yu; Wang, Dong-Jin; Gu, Hong-Wei; Wang, Xiao-Ming (Frontiers in Oncology, 2022)
Cancer is one of the most serious diseases threatening human health, so it is particularly important to develop effective tumor targeting drugs. As the first CDK4/6 inhibitor, palbociclib effectively inhibits tumor proliferation by blocking the cell cycle to the G1 phase. 10-HCPT is a Topo Ⅰ inhibitor, however, its clinical application has been greatly limited due to its high toxicity. Based on the successful development of double target inhibitors, three novel palbociclib derivatives (HP-1, HP-2 and HP-3) were designed and synthesized from Palbociclib and 10-HCPT, and their biological activities were investigated. At first, the possible binding sites of the three compounds to Topo I and CDK4/6 were predicted by molecular docking. Then, we evaluated the anti-proliferative effects of the three palbociclib derivatives. In general, human lung cancer cells were more sensitive to HP-1, HP-2 and HP-3, especially NCI-H460. In addition, cell cycle arrest and apoptosis induction were investigated by flow cytometry. The three palbociclib derivatives, especially HP-1, had obvious cell cycle arrest phenomenon on NCI-H460 cells, and induced apoptosis of NCI-H460 cells significantly. In the end, it was proved that these three drugs had obvious cyclin-dependent kinase inhibitory activities. In short, all the data showed that HP-1, HP-2 and HP-3 could play anti-cancer roles by acting on dual targets, and had the characteristics of high efficiencies and low toxicities, which opened up a new idea for the study of palbociclib derivatives.